ANALISIS MATERIAL REMOVAL RATE PADA PROSES CNC MILLING TERHADAP MATERIAL AISI 1045 - Ival Ival; Zaldy Kurniawan; Erwanto Erwanto (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
The result of a large material removal rate is the desired goal in the CNC MORI SEIKI MV40-m process, the right settings for the MORI SEIKI MV40-m CNC process must be adjusted so that a large workpiece Material Removal Rate response is obtained. The research that has been conducted aims to determine which parameters contribute greatly to the Material Removal Rate and to determine the effect of variations on each parameter. The parameters of the machining process that were varied were the cutting speed and the infeed depth. The experimental design is based on the Taguchi method and is in the form of an L9 (32) orthogonal matrix. The analytical method used is Taguchi. The experiment was carried out randomly 3 times in order to produce more optimal results and prevent disturbances that occurred during the machining process. The results showed that the parameter that contributed greatly to the Material Removal Rate was cutting speed, which was 7.2%. To obtain a large workpiece Material Removal Rate, the cutting speed is set at 180m / min and the infeed depth is set at 0.26 mm.